Susceptibility to e-cigarette adoption among tobacco-naïve youths: a cross-sectional study in Shenzhen, China - Ruilin Yan; Yanhong Liu; Li Huang; Yanrou Li; Yun Huang; Jing Tong; Yongzheng Deng; Qing Yuan (Frontiers Media S.A., 2024)
BackgroundThe rise in e-cigarette use among youth is a significant global public health issue. It is important to identify those at increased risk and implement effective strategies to reduce e-cigarette popularity among the youth.ObjectiveThis study aims to identify predictors of e-cigarette uptake in youths with no prior tobacco use, considering individual, familial and the broader societal environmental factors.MethodsFor this investigation, a group of 2,487 tobacco-free youths was selected from 15 high schools in Shenzhen, China. Susceptibility to e-cigarettes was determined by assessing the possibility of future use and the openness to trying e-cigarettes if presented by friends. Both chi-square tests and logistic regression were applied to identify factors linked to susceptibility to e-cigarette use.ResultsAmong the respondents, 5.5% (n = 136) were found to be susceptible to e-cigarette use. The analysis revealed factors tied to this risk: perceptions of e-cigarettes, the impact of vaping peers, paternal parenting styles, the extent of social support, exposure to messages both for and against e-cigarettes use, and secondhand smoke (SHS) exposure. Youths who downplayed the addictive nature of e-cigarettes (aOR = 2.01; 95% CI: 1.14-3.55; p = 0.016), those with friends who engaged in vaping (aOR = 3.43-7.64; 95%CI: 2.36-20.42; p < 0.001), those experiencing over-protective or rejective maternal parenting (aOR = 1.68-3.01; 95%CI: 1.11-5.77; p = 0.001-0.014) or rejective paternal parenting (aOR = 3.63; 95%CI: 1.99-6.59; p < 0.001), those aware of e-cigarette advertisements (aOR = 1.82; 95%CI: 1.28-2.60; p = 0.001), and those exposed to SHS at home (aOR = 1.68; 95%CI: 1.17-2.41; p = 0.005) or at public places (aOR = 1.72-1.79; 95%CI: 1.21-2.57; p = 0.002-0.003) were more prone to e-cigarettes. In contrast, youths who believed using e-cigarettes reduces one's attractiveness (aOR = 0.34; 95%CI: 0.16-0.72; p = 0.005) or perceived that vaping made social interactions less enjoyable (aOR = 0.26; 95%CI: 0.12-0.58; p = 0.001), those who benefited from high social support (aOR = 0.30-0.60; 95%CI: 0.17-0.97; p < 0.001), and those who noticed message about e-cigarettes' adverse consequence (aOR = 0.54; 95%CI: 0.38-0.77; p = 0.001) were less likely to be inclined toward e-cigarette use.ConclusionThe propensity of the youth to e-cigarette usage is shaped by a multiple element. An all-encompassing strategy that addresses the individual, familial, and the broader societal aspects is imperative for the effective prevention of e-cigarette initiation among youth.